Informacijska zasebnost pacientov v zdravstvu - Bohinc, Marija (Obzornik zdravstvene nege, 1999)
Modern societies pay a great deal of attention to the protection of personal data, i.e. to information privacy. Espe-cially important are legal, technical and ethical aspects of personal data protection. The article deals with some regulations, principles and professional background from this field and with problems encountered in practice.
Keywords: Computer security; Confidentiality; health care; informacijska zasebnost; informacijski sistemi; Information systems; Legislation and jurisprudence; Medical records systems, computerized; pacienti; privacy; zasebnost; zaupnost; zdravstvo